PENGARUH CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE - Annisa, Nuralifmida Ayu; Kurniasih, Lulus (JURNAL AKUNTANSI DAN AUDITING, 2012)
This study aims to find out how the influence of the corporate governance of tax avoidanceactivity in companies listed on Indonesia Stock Exchange in 2008. The samples are publiclytraded company listed on the Indonesia Stock Exchange in 2008 as many as 200 companies. Thisstudy uses data analysis and regression analysis of the elements of corporate governance and taxavoidance. The results of this study show that the elements of corporate governance that consist ofaudit quality and audit committee significantly influence the activity of tax avoidance as measuredusing proxy book tax gap. Other results show that the tax avoidance activity as measured withproxy book tax gap are not affected significantly by institutional ownership and board ofcommissioners. Limitation of this study is not to use each type of industries as control variable socan’t identify the direct effect from type of industry on tax avoidance. Another limitation of thisstudy is use corporate governance’s proxy separately, so it can’t capture the full effect ofcorporate governance.Keywords:corporate governance, ownership structure, board of commissioners, audit committee,tax avoidance, book tax gap.